Spory wokół Trybunału Konstytucyjnego w Polsce w latach 1981-1985 - Mażewski, Lech (Czasopismo Prawno-Historyczne, 2018)
The creation of the Constitutional Tribunal (1981, 1985), instead of a separate chamber of the Supreme Court, was accompanied by numerous discussions and sometimes even disputes. The process took place between 1981 and 1985. It was decided that in case of analyzing whether a law is constitutional and legal, the most important element is the existence of an independent state body such as the Constitutional Tribunal. Moreover, jurisdiction activity was brought into the purview of the Tribunal. In order to achieve this, the Parliament (Polish Sejm) had to enact a proper statutory law and to select judges for the Constitutional Tribunal. However, regardless of all the legal deficiencies which accompanied the legal regime of the new body, it should be considered an important step in the construction of the constitutional judiciary in Poland. The jurisdiction activity of the Tribunal between 1986 and 1989 also attests to that. The constitutional legislator created such a model of the Tribunal which prevented it from being fully recognized as a constitutional court. The rationale behind this was the necessity of preserving the Parliament’s superior position in the system of state bodies. The Tribunal was rather founded as a body to analyze the legality of law in order to ensure the supremacy of constitutional acts in the system of law sources. However, even such a legal solution had its significance from the point of view of protection of civil and political rights as well as of civil liberties.